Imam Muqatil Bin Suleiman and his Methodology in his Book Al-Wajuh wa Al-Nadh’ir in the Great Quran - Ibrahim , Abdullah (Islamic Sciences Journal, 2023)
ABSTRACT Prais be to Allah whose grase is the best goodies. Prayers and peace be upon the master of the messengers Muhammad, his family, and companion as a whole. As for after, the science of faces and isotopes is one of the science of the Quran which is dealing with interpreting the words of its wise verses with the assistance of the causes of the descent and linguistics. The meaning of this science refers to a world which is mentioned in differend places inside the Quran with the same pronunciation and the same analysis, and it has a different meaning in any of these different places. Thus, the science of isotopes is the name of words, and faces: is the name of meanings . the first person who speaks in this scince is the great companion Abdullah Bin Abbas-may Allah be blessed with them-However, the first sorter in this science who is known by scientists is Imam Muqatil Bin Sulaiman Al-Balkhi who died in(150H) in his book entitled(Faces and Isotopes in the Holy Quran). This book includes (176) words, the first word is (the guidance) and the last word is (Above). I have studied four of its models in the current study.